CORAK PEMIKIRAN TEOLOGI ISLAM (STUDI KASUS PADA TOKOH AGAMA DI BENGKULU UTARA) - Syahril Syahril (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: This research by using qualitative research methodologies. The results of this study concluded that the idea of religious figures of Islamic theology in North Bengkulu looked sense can serve to obtain clarity on the issues of divinity in the importance of reason necessary for aspects of Islamic teachings are informed by revelation. Revelation is a source of knowledge about God, good and evil, as well as the obligation of mankind to do good and keep away evil sense function, without revelation will bringheavy burden in human life. Meaning here, religious leaders in North Bengkulu wearing traditional pattern, although the one hand there is the rational or principled Mu’tazila. Thought religious leaders about human freedom and the absolute will of God, trend of thought religious leaders in North Bengkulu more directed to understanding of the authority and the absolute will of God, as to which are held by Asy’ariyah understand, because humans trying to be balanced with the absolute power of God. Human beings are not creation that freely, but free man limited by God as a limited human being with age. This indicates that humans are limited and everything has an end. Thought religious leaders in North Bengkulu on qadha and qhadar which are already provisions inviolability, humans could only surrender and resignation to God. Thus they tend to be closer to understanding Asy’ariyah. Thought religious leaders on the nature of God, they adopts Asy’ariyah, they’ve studied the attributes of God. By reading and realize their self-interest as human beings would study the nature of God, then verily Allah can describe it is there. Factors affecting patterns of thought religious leaders of the Islamic theology in North Bengkulu, namely their learning that be a forum to understand the Islamic faith, boarding schools in Bengkulu Utara place of formal education and non-formal and social situations such as differences in environmental conditions and impact of globalization very closely influence in shaping the understanding of Islamic theology in North Bengkulu.